ANALISIS KINERJA LAYANAN FINANCIAL TECHNOLOGY (FINTECH) PADA PENGGUNAAN APLIKASI PINJAMAN ONLINE - Lisna Purnama Lase; Chasvar Antonius Manalu; Hendra Jonathan Sibarani (SUAN PUBLISHER, 2024)
Financial Technology (FinTech) is one of the most widely used financial applications by the public to fulfil all their needs. In addition, this online loan process is very easy and fast so that it really helps people who are pressed by economic needs, but because of the increasing use of online loans throughout the community without exception, there are problems and unrest in the community in replacing money that has been borrowed in online applications and of course has an impact on unethical billing and also various threats received by customers. Another problem is that financial problems are one of the factors that influence people's mindset to be able to survive in overcoming all basic human needs. In this situation, some people end up using online loans to overcome financial problems. This research uses a qualitative approach by using people's experiences as research data and using references from research results that provide an assessment of online loan applications as a basis for analysing the performance of financial technology services